2010
DOI: 10.1002/dc.21508
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy and safety of fine‐needle aspiration biopsy of the parapharyngeal space

Abstract: Fine-needle aspiration (FNA) biopsy of the parapharyngeal space (PPS) is a diagnostic challenge and sampling is often done without image guidance, often trans-orally. Primary PPS tumors are rare, and there is a broad differential diagnosis. The accuracy of PPS FNA, in particular without CT-guidance and using liquid-based cytology (LBC), has not been well studied. Pathology records from our institution (a 1,100 bed Canadian academic tertiary care centre) were searched to identify all patients who underwent PPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…FNAC of PSS tumors is performed for lesions of the prestyloid PPS and may allow for the differentiation of salivary gland malignancies. Needle biopsy of the poststyloid PPS carries the risk of vascular complications (22), and its use is also limited in cases of the diagnosis of hemorrhagic specimens in paragangliomas and hypocellular specimens in schwannomas (23,24). A flow chart of the complete preoperative examination process is presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…FNAC of PSS tumors is performed for lesions of the prestyloid PPS and may allow for the differentiation of salivary gland malignancies. Needle biopsy of the poststyloid PPS carries the risk of vascular complications (22), and its use is also limited in cases of the diagnosis of hemorrhagic specimens in paragangliomas and hypocellular specimens in schwannomas (23,24). A flow chart of the complete preoperative examination process is presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic performance of ultrasound‐guided FNAC for PPS tumors was shown to be relatively low . Moreover, no studies have shown the usefulness of FNAC in cervical schwannomas, and the accuracy of FNAC has been reported to be 20.0%‐30.3% . FNAC is likely not essential in cases of suspected schwannoma, because cell sampling per se is not only very difficult due to strong intercellular binding but also carries the risk of injury of the involved nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Reported sensitivities are 64%‐82% in a routine diagnostic setting and even higher in study settings, and detection of allele frequencies as low as 0.1% can be achieved. Here, sampling error may play a role since mutated cfDNA molecules might not be present in each replicate . Therefore, samples should always be analyzed in triplicates if low allele frequencies are expected …”
Section: Different Methods For Mutation Detection In Routine Diagnosticsmentioning
confidence: 99%
“…119 The use of locked nucleic acid (LNA) probes further enhances the sensitivity for mutations as the amplification of wild type alleles is suppressed. 120 Physical partitioning of PCR reactions can be achieved by chip-based systems using microwell plates (Quantstudio 3D, Thermo Fischer Scientific) 47,117 or microfluidic systems for parallel PCR reactions (Fluidigm) 121,122 as well as by oil emulsion-based droplet systems, including droplet dPCR (Bio-Rad), 123 picoliter droplet-based dPCR (RainDance), 100 and BEAMing. 124,125 Comparable to qPCR assays, the ability of dPCR as well as ddPCR to perform multiplex analysis is limited.…”
Section: Dpcr and Ddpcrmentioning
confidence: 99%
See 1 more Smart Citation